A study on user's involvement in the design phase of system development life cycle (SDLC) / Nur Hazliana Mohamad Nor - Mohamad Nor, Nur Hazliana (2012)
Recently, the involvement of users in the system development has been increasingly turned into a major concern, specifically from what the general observation that has been made. However in Malaysia, those concerns still has been neglected mostly among the engage persons whose involve in the system development, especially the system or software developers. Users' involvement is considered to be rare and quite uncommon in software development organizations. As for certain companies outside Malaysia, the involvement of users has become more and more important as it will bring few benefits as well as will cut the cost and reduce the time consume in developing desired system. Thus in this research, a focus will be given to the users involvement practice specifically in the design phase of the system development. A detail research will be conducted for users' involvement in the design phase itself and this will fall in the scope of Human Centered System Development Life Cycle where once again will be focus on the design phase. First of all, the research will be focused in determining the involvement of users particularly in the design phase of system development. After that, from the interviews conducted on eight persons from eight companies whose involved in the system design, particularly including the system or software developers, IT programmers, system analyst as well as system and software designers. From those interviews, an evaluation has been made to determine the factors that encourage users' involvement particularly in the design phase of SDLC, by using the method for analyzing qualitative data manually. Finally, a guideline will be developed at the end of the research in order to improve the system design by the involvement of users in the design phase.